Relationship Between C-Reactive Protein/Serum Albumin Ratio, Neutrophil/Lymphocyte Ratio, and ANCA-Associated Vasculitis Activity: A Retrospective Single Center Cohort Study - Tian, Yao; Liu, Na; Yin, Hui; Duan, Lihua (Frontiers in Medicine, 2022)
Objectives: To evaluate the role of C-reactive protein/albumin ratio (CAR) and neutrophil/lymphocyte ratio (NLR) in newly diagnosed ANCA patients and examine their clinical significance. Methods: Data from 79 untreated newly diagnosed ANCA patients were collected and 76 health examination subjects were included in the healthy control group. All clinical characteristics of ANCA patients were extracted from their medical records. The NLR, CAR, and MPV levels of ANCA patients and the healthy controls were compared and the correlation between these markers and clinical characteristics was analyzed. Patients were then divided into two groups based on BVASs. The correlation between NLR, CAR, and MPV and disease activity was analyzed and their effects on the cumulative survival rate were analyzed. Results: Compared with the healthy control group, elevated CAR, NLR, and MPV were observed in ANCA patients. CAR (r = 0.701, P < 0.0001) and NLR (r = 0.369, P < 0.05) were positively correlated with the BVAS while MPV did not show any significant correlation (P = 0.85). The optimal cutoff value for disease activity evaluation using CAR was 0.80 (sensitivity: 85% and specificity: 82%, P < 0.05). The optimal cutoff value for disease activity evaluation using NLR was 5.15 (sensitivity: 66% and specificity: 72%, P < 0.05). Kaplan–Meier survival analysis revealed that the all-cause mortality rate was higher in patients with CAR ≥ 0.8 than in patients with CAR < 0.8 (P < 0.05). Patients with low NLR also showed a lower cumulative survival rate (P < 0.05). Conclusions: NLR and CAR can reflect the inflammatory response and disease activity in ANCA patients, while MPV is not significantly correlated with disease activity in ANCA patients. The all-cause mortality rate was higher in patients with high CAR and NLR than in patients with low CAR and NLR.